(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Through the new tehnalogies of the shrines, comunicative communication occurs in addition to providing visitors with comfort. The concept of modern heating design of shrines is also distinguished by the fact that it requires an hos creative approach to itself. Research on the factors affecting the solutions of the concept of modern heating design, the search and research of functional interior elements through technalogies based on modernity in accordance with the needs and interests of this modern heating.